Risk perception, attitude, and practice related to COVID-19: A cross-sectional study among 1085 Iranian healthcare workers. (October 2021) - Roshanshad, Romina; Roshanshad, Amirhossein; Molavi Vardanjani, Hossein; Mashhadiagha, Amirali; Mobarakabadi, Maryam; Hoveidaei, Armin; Hoveidaei, Amir Human
Abstract: Backgrounds: Healthcare workers are at risk of mental illness during COVID-19 pandemic. We investigated the level of perceived risk and adherence to preventive behaviors regarding COVID-19 among medical students and physicians. Materials and methods: We conducted an online nationwide cross-sectional survey among Iranian physicians and medical students. We collected data regarding perceived risk, perceived stress scale (P·S·S.), attitude, practice, and information sources. We assessed the association of four main outcomes (risk perception, P·S.S. score, attitude, and practice) with demographic variables. Results: A total of 1085 participants with an overall fear score of 6.48 ± 2.29 out of 10 filled the questionnaires. Older and more educated participants had a higher risk perception level and adherence to protective measures. In contrary, participants in lower-risk workplaces had lower risk perception scores. Main sources of information did not affect the scores of risk perception, P·S·S., and practice. Higher risk perception scores were observed in those with higher practice and P·S.S. scores. Contrary to risk perception, the P·S.S. score was not affected by many of the demographic variables, except gender. The most positive attitude was observed in individuals with a higher level of trust in governmental information sources. Participants with higher P·S.S. scores adhered more to protective measures. Conclusion: Risk perception had the greatest impact on adherence to preventive behaviors. Therefore, policymakers should consider perceived risk as a predictor of the extension of the pandemic. Both risk perception and P·S.S. reflect the severity of fear from COVID-19; however, P·S.S. is less affected by sociodemographic and workplace characteristics. Highlights: Risk perception had the greatest impact on the adherence to preventive behaviors. Risk perception and perceived stress both reflect severity of fear from COVID-19. P·S.S. is less affected by sociodemographic and workplace characteristics. Using a source of information would not affect the attitude of the H·C·W.s. Trust in a specific source of information might affect the attitude of the H·C·W.s.